Acute ST-elevation myocardial infarction: are men and women particular cases of STEMI ?. (2nd July 2022) - Duarte, F; Coutinho, I; Barradas, M I; Oliveira, L; Serena, C; Fontes, A; Monteiro, A; Machado, C; Santos, E; Pelicano, N; Pacheco, M; Tavares, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: ST-segment elevation myocardial infarction (STEMI) has high levels of morbidity and mortality. Multiple risk factors may contribute to clinical outcomes and some studies demonstrate gender-related differences in baseline characteristics and in-hospital management. Purpose: To access the difference in clinical characteristics and prognostic outcomes between men and women who were admitted in our Cardiac Intensive Care Unit with STEMI diagnosis. Methods: We retrospectively analyzed 121 non-consecutive patients with STEMI during a mean follow-up period 135 ± 31 weeks. We accessed baseline characteristics and time course of events (symptom onset-to-door admission; time to first EKG; time to fibrinolytic therapy; door-to-cath lab time and time from fibrinolytic therapy to PCI (for patients transferred from another centers). Primary endpoint (PE) was a composite of in-hospital cardiovascular death, arrhythmic events or STEMI evolution in Killip-Kimbal III or IV. Secondary endpoint (SE) was in-hospital major bleeding events, considered intracerebral hemorrhage, cases of hemodynamic compromise or requiring a blood transfusion. Tertiary endpoint (TE) included admissions to the emergency department or hospitalization by heart failure decompensation, acute or chronic coronary syndromes and all-cause mortality. Results: Of the 121 patients, 102 were male (84.3%) and 19 (15.7%) female. The mean age was 58.3 ± 12.7 years and women had a superior mean age (69.8 ± 12.2 years) vs. Men mean age 56 ± 11.6 years. Hypertension was more prevalent in women (84.2% vs. 47.1%, respectively; p 0.003) and also diabetes – 36.8% of women had type 2 diabetes (vs 10.8% of men) and 5.3% of these female patients requires insulin therapy (vs 2% of men; p 0.021). According to Charlson Comorbidity Index (CCI), women had a higher disease burden with 73.7% of them included into the moderate or severe group of mortality risk, compared to 42.2% of men (p 0.014). Conversely, less women smoke (31.6% vs. 82.2%; p <0.001) and less frequently chest pain was the onset symptom (78.9% vs. 95.1%; p 0.04). Time since symptom onset to door admission was estimated on 510 ± 1149 minutes and the mean women delay was superior (557 ± 858 minutes). Regarding to in-hospital hemorrhagic events (secondary endpoint), female patients had a statistically significant higher risk (22.2% vs. 7.1%, p 0.045), independently of hypertension, diabetes or anticoagulant therapy (r=0.249; ANOVA p-value < 0.005), but it was associated with higher CCI (p 0.033). No other gender differences in outcomes or survival function were observed. Conclusion: Our study demonstrates gender-related differences among patients with STEMI. Indeed, women were older, had more clinical cardiovascular risk factors and tend to delay hospital admission after symptoms onset. Secondary endpoint was statistically more frequent in women, but no other differences in outcomes were observed.